Introducing the new Health Visitor Research Champions. (2nd August 2019) - Mugweni, Esther; Baldwin, Sharin; Meachin, Clare; Adams, Cheryll
Abstract : In 2018, the Institute of Health Visiting collaborated with the National Institute for Health Research to appoint Health Visitor Research Champions. This article describes the role of Research Champions and highlights their successes to date